1985
DOI: 10.1002/oca.4660060406
|View full text |Cite
|
Sign up to set email alerts
|

Traffic regulation of an underground railway transportation system by state feedback

Abstract: SUMMARYThe commonly used state-space models for the traffic description of urban underground railway lines are not suitable for practical on-line control. On the other hand, the proposed orginal linear formulation is very convenient for optimal state feedback control implementation. Results of simulations relative to a theoretical line as well as to the Brussels Railway lines show the benefit to be expected using this new formulation for on-line traffic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
11

Year Published

1987
1987
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 2 publications
0
16
0
11
Order By: Relevance
“…The metro system can be modelled by a system of equations in discreet time [9], 1 1 It has been demonstrated that metro lines are unstable in presence of disturbances if no control action is applied for correcting the itinerary of the trains [1,2]. Such kind of control action could be performed by manipulating stop times or in-between station running times.…”
Section: Traffic Dynamical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The metro system can be modelled by a system of equations in discreet time [9], 1 1 It has been demonstrated that metro lines are unstable in presence of disturbances if no control action is applied for correcting the itinerary of the trains [1,2]. Such kind of control action could be performed by manipulating stop times or in-between station running times.…”
Section: Traffic Dynamical Modelmentioning
confidence: 99%
“…The dynamics of metro line systems have been deeply studied by several researchers [1][2][3][4][5][7][8][9][10]. Most of these dynamical models are based on the Sasama and Ohkawa [9] linear model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several passenger flow models have been proposed to estimate the dwelling time [1][2][3][4][5][6][7][8][9][10][11][12]. This is not a trivial task given that the passenger flow in the different boarding and alighting zones is not homogeneous [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches model the passenger boarding and alighting process [1,3,6]. In [9,12], the authors use space-state approaches to estimate the passenger flow for traffic control applications. Xu et al [10] developed a probabilistic approach to describe the distribution of the lines in the platforms using queueing and Markov theory and taking into account the geometry of the platform.…”
Section: Introductionmentioning
confidence: 99%